Teacher Strategy in Character Formation Through the History of Islamic Culture Subject - Nasichatu Muslimatin, Siti Rahayu (EDU-KATA, 2024)
This research aims to understand teachers' strategies in character building through Islamic cultural history subjects at SMA Muhammadiyah 1 Taman Sidoarjo. Researchers in the study used qualitative research. Research uses a constructive paradigm. The data collection techniques in this research include observation, interviews and documentation. In this research, the researcher is the informant, where the presence of the researcher is very important. Data analysis is inductive/qualitative in nature with stages of data reduction, data display and conclusion drawing, and qualitative research results emphasize meaning rather than generalization. The formation of student character is based on all aspects of education. Character education is designed to shape students into individuals who have noble character, have positive characteristics and habits, and behave in accordance with Islamic and national values. The strategy of the Islamic Cultural History (SKI) teacher at SMA Muhammadiyah 1 Taman Sidoarjo in efforts to build student character focuses on morals, morals and ethics in learning materials. Teachers use an approach that involves telling inspiring stories from Islamic history, reflective discussions, on characters in everyday life. Teachers in teaching to instill values ​​such as honesty, hard work and responsibility. Teachers in learning also have several obstacles in their efforts to build student character, such as student background, time constraints, the environment outside of school, diverse student responses.